ANALISIS PERFORMA TURBINE OIL COOLER DI PLTU ASAM ASAM UNIT 1 - Akhmad Syarief; Rangga Mahesa (Universitas Lambung Mangkurat, 2021)
Performance analysis of a heat exchanger is a method used to determine the performance of a heat exchanger. The purpose of this study is to determine the heat balance value, heat transfer coefficient, pressure drop, and calculate efficiency. In this study discussed about shell and tube heat exchanger type which serves to cooling Turbine Generator shaft bearing oil with Cooling Tower water. The data studied for 1 month in September and 2 data point were taken in 1 day, namely at 3:00 a.m. (WITA) and 12.00 WITA (daytime) and not describe the system as a whole. The method in this study using the principles of heat transfer and the LMTD approach (logarithmic Mean Temperature Difference) and the kern method. The results of this study indicate that the average heat balance (Q) is 159,798.9 Btu/dhr with the heat transfer area (A) of 580,172 ft2 and the average heat transfer coefficient equal to 10,965 Btu/hr.ft2.oF. For the reduction of heat exchanger is still within the allowable limit, namely with an average of 0.01 kg/cm2. As for the efficiency of the heat exchanger observed it has an average which is quite low at 51.95% but still recommended to operate.